EFFECT OF NERVE CONDUCTION STUDIES IN HYPOTHYROIDISM - AN OBSERVATIONAL STUDY - A, Lalithamma; S, Vadivel; W, Johnson; V, Jacob; T, Chitra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This observational study was conducted during the year 2016–2017 to assess the electrodiagnostic evidence of peripheral nerve dysfunction among newly diagnosed hypothyroid patients attending a tertiary care hospital and to find the effect of hormonal treatment after short duration. Methods: An observational study was conducted in 25 newly diagnosed hypothyroid patients with the age group of 20–60 were included. After obtaining informed consent, all participants were examined with electrodiagnostic workup performed at the initial time of diagnosis and after short duration for median and ulnar nerves of upper limb by (NeuroStim -NS2, EMG/EP/NCV, and MEDICAID SYSTEMS). Electrophysiological parameters such as distal motor latency, amplitude, and conduction velocity were evaluated. Results: The mean age of study population was 42.7±12.1 (23–61) years. The mean values of nerve conduction velocity of motor and sensory median before the treatment were 42.8±15.7 and 40.13±4.19 and motor and sensory ulnar before treatment were 41.18±22.4 and 39.46±11.9. The mean values of nerve conduction velocity of motor and sensory median after treatment were 53.35±4.7 and 57.3±5.6 and motor and sensory ulnar After treatment were 54.56±2.99 and 54.09±12.17. The result of the study. Shows that there were reduction of conduction velocity before treatment and statistically significant after 3 months duration of treatment with appropriate doses. Conclusion: After treatment, total triiodothyronine, total thyroxin, free triiodothyronine, free thyroxin, thyroid-stimulating hormone, and median and ulnar nerve motor and sensory functions were normal with appropriate treatment. The involvement of sensory fibers is more than that of the motor fibers.